Sodium borohydride for solid-state green hydrogen export - Ibrahim, Ainee (Curtin University, 2024)
Sodium borohydride is a powder that can be used to store and export energy as hydrogen. The technoeconomic viability was assessed, which determined sodium borohydride is competitive to other hydrogen export methods. Additionally, the hydrogen release of sodium borohydride was investigated to high pressures suitable for hydrogen re-fuelling stations. After hydrogen release, the regeneration of sodium borohydride was explored using metal hydrides. This demonstrated potential low-cost pathways for recycling the hydrogen export material.